PERFORMANCE INDEX DERIVED FROM CHLOROPHYLL A FLUORESCENCE INDUCTION CURVE INDICATES THE SALT INDUCED GRAIN YIELD LOSS IN WHEAT - Z. Sun; S. Liu; J. Fan; Q. Li; K. Wang; M. Guo; G. Zhang; L. Ren; G. Zheng; T. Ma; H. Pu; J. Cai; et al. (Journal of Animal and Plant Sciences, 2018)
Soil salinity severely limits plant growth and reduces grain yield in wheat ( Triticum aestivum). Forty-three local wheat cultivars and breeding lines were exposed to a salt treatment (by adding 200 mM NaCl solution) for two weeks, and chlorophyll content and chlorophyll a fluorescence parameters, performance index (PI) and maximum quantum yield of PS II (Fv/Fm) were determined just after salt treatment. It was found that salt stress resulted in different reductions in chlorophyll content and chlorophyll a fluorescence parameters among the 43 wheat cultivars and breeding lines. The salt induced decrease in PI and Fv/Fm varied in a large range among 43 wheat cultivars. The grain yield loss induced by salt stress was mainly due to the decrease in grain weight in wheat. It was concluded that PI was a good parameter for screening genotypes with higher grain weight and grain yield under salt stress. characteristic (Strasser et al. 2004; Li et al. 2014a,
Keywords: Chl a fluorescence; Triticum aestivum; salinity; grain yield.